Development And Validation Of Questionnaire To Assess Knowledge, Attitude And Perception Among Nurses On Responsibility And Patient Management Related To Blood Transfusion - Chew, Poh Ling (2019)
Introduction: In modern clinical practice, transfusion of blood products was often used to improve the hemodynamic profile and clinical condition of patients. However, error in blood transfusion practice jeopardizing safe transfusion and may lead to severe and life-threatening consequences to the patients. Haemovigilance program over the year continue to report, human error is the greatest risks in safe blood transfusion. In Malaysia, reported transfusion reaction due to incorrect blood component transfusion was 0.73%, and the majority (80%) occur in the clinical ward. Nurses play a central role in ensuring safe blood transfusions, as more than half of the steps in blood transfusion are dependent on the nurse's awareness and skills. Sufficient knowledge among nurses were essential to ensure safe practice in patient care and improve patient safety. Besides professional knowledge, good attitudes and perception of health care worker can affect safe behaviours practice and quality of patient care. However, there was no validated questionnaire available to assess nurses’ knowledge, attitude and perception in patient management related to blood transfusion. Objective: To develop and validate a questionnaire about the knowledge, attitude and perception among nurses on blood transfusion management. Methods: A cross-sectional study was conducted among nurses at the Clinical Complex (CC) of Advanced Medical and Dental Institute (AMDI), Hospital Kepala Batas and Hospital Seberang Jaya, Penang, Malaysia. The study used a self-administrated questionnaire that take approximately 30 minutes to complete. The validation involved content validation, exploratory factor analysis for construct validity, internal consistency and test retest for reliability.